Detection of acute pulmonary embolism: feasibility of diagnostic accuracy of MRI using a stepwise protocol - Hosch, Waldemar P.; Schlieter, Martin; Ley, Sebastian; Heye, Tobias; Kauczor, Hans-Ulrich; Libicher, Martin (Emergency radiology, 2014)
Multidetector computed tomography (MDCT) has become the imaging method of choice in patients suspected of having pulmonary embolism (PE) but has the inherent limitation of radiation dose and the side effects of contrast agents. The purpose of the study was to assess the feasibility of a stepwise MRI protocol in the clinical setting of acute PE. The stepwise approach should make it possible to diagnose acute PE in critically ill patients using fast MR sequences and included the option to add comprehensive sequences when patients were stable. Forty-five patients with acute PE (26 men, 19 women; 41 ± 16 years) were included in this prospective study. The diagnosis was initially confirmed by MDCT as gold standard. MRI at 1.5 T was subsequently performed without any delay in medical treatment. The MRI protocol proceeded stepwise from robust to detailed imaging techniques (i.e., from TrueFISP and single shot HASTE sequence to MR perfusion and 3D-MR angiography) if the patient was able to tolerate additional imaging time. Diagnostic accuracy was evaluated on the central (lobar) and peripheral (segmental) levels. The complete MR protocol was applied in 40 of the 45 patients (88 %). In the remaining five patients with severe dyspnea the diagnosis of acute PE was established by using fast TrueFISP sequences that were insensitive to respiratory movement. All five patients suffered from a major central PE. Highest sensitivity was achieved by MR perfusion (lobar, 98 %; segmental, 95 %). Real-time TrueFISP and MR angiography showed the highest specificity (lobar, 90-100 %; segmental, 95-97 %). The combination of all MR sequences matched closely the results of MDCT (lobar: sensitivity 98 %, specificity 100 %; segmental: sensitivity 95 %, specificity 97 %). MRI using a stepwise protocol is a promising approach for diagnosing acute PE. The protocol can be tailored for dyspneic patients with central PE using real-time MRI sequences. The diagnostic accuracy for peripheral PE can be improved by using combined MR techniques, achieving comparable results to MDCT.
Gesehen am 29.10.2021
Published online: 27 November 2013